Insulin Signaling as a Key Moderator in Myotonic Dystrophy Type 1 - Nieuwenhuis, Sylvia; Okkersen, Kees; Widomska, Joanna; Blom, Paul; 't Hoen, Peter A. C.; van Engelen, Baziel; Glennon, Jeffrey C. (Frontiers in Neurology, 2019)
Myotonic dystrophy type 1 (DM1) is an autosomal dominant genetic disease characterised by multi-system involvement. Affected organ system include skeletal muscle, heart, gastro-intestinal system and the brain. In this review, we evaluate the evidence for alterations in insulin signalling and their relation to clinical DM1 features. We start by summarising the molecular pathophysiology of DM1. Next, an overview of normal insulin signalling physiology is given, and evidence for alterations herein in DM1 is presented. Clinically, evidence for involvement of insulin signalling pathways in DM1 is based on the increased incidence of insulin resistance seen in clinical practice and recent trial evidence of beneficial effects of metformin on muscle function. Indirectly, further support may be derived from certain CNS derived symptoms characteristic of DM1, such as obsessive-compulsive behaviour features, for which links with altered insulin signalling has been demonstrated in other diseases. At the basic scientific level, several pathophysiological mechanisms that operate in DM1 may compromise normal insulin signalling physiology. The evidence presented here reflects the importance of insulin signalling in relation to clinical features of DM1 and justifies further basic scientific and clinical, therapeutically oriented research.